The Study of English Loan Word Phonology in Urdu - Khan, Nayab Waqas; Rizvi, Syeda Zahida; Farooq, Mahwish (International Journal of Psychosocial Rehabilitation, 2020)
This paper elucidates the exploration of loan word phonology in Urdu language. It is an attempt to examine loan words in Urdu language specifically that have been taken from English language. The paper attempts to trace the innateness of loan words in Urdu and its gradually becoming “native” through the phonological phenomena of variation in vowels, insertion, borrowing, deletion of vowels and conversion in morphosyntactic features of the loan word phonology. The words studied; are the most frequently used in Urdu language by native speakers so that these loan words have become an integral part of daily conversation these words are spoken under the umbrella of Urdu words’ pronunciation influence. The paper culminations with an analysis and discussion of the factors behind naturalization of loan words in a specific language.